Evaluation of serum amylase and lipase in diagnosed Covid-19 survivors in a North Indian Hospital, Lucknow, India - Nabeela Usmani; Mukhtar Ahmad; Saba Khan; Mohammad Mustufa Khan; Haseeb Ahsan; Sadaf Parveen; Roshan Alam (Acta Biochimica Indonesiana, 2023)
Background: Coronavirus disease 2019 (Covid-19) is a novel disease caused by coronavirus-2 that causes severe acute respiratory syndrome (SARS-CoV-2). Although it primarily affects the respiratory system, the virus may also target the pancreas. It was suggested that upregulation of angiotensin-converting enzyme II (ACE-II) cell receptors or inflammatory cytokines play a major role in predisposing pancreatic injury in SARS-CoV-2 patients. Our aim was to conduct a critical evaluation of in order to provide an insight into the possibility of pancreatic injury. Methods: A case control study was conducted in the Department of Biochemistry IIMS&R, Integral University, Lucknow. Two groups of subjects (70 adults consisting of 35 Covid-19 survivors and 35 controls) aged between 35 to 70 years were selected for the study with mild to moderate Covid-19 diagnosed using RT-PCR/rapid antigen test and a control group of healthy individuals without history of Covid-19. The serum amylase was determined by the direct substrate method and serum lipase by the turbidimetric UV method using a semi-autoanalyzer. Results: The study showed that the serum amylase (p=0.023) and lipase (p=0.002) levels were significantly elevated in Covid-19 patients compared to the control subjects. The findings indicated that Covid-19 patients had a substantially higher mean serum amylase and lipase levels than the control subjects. Conclusions: The Covid-19 patients are prone to pancreatic injury.